Range edges of North American marine species are tracking temperature over decades. (18th April 2021) - Fredston, Alexa; Pinsky, Malin; Selden, Rebecca L.; Szuwalski, Cody; Thorson, James T.; Gaines, Steven D.; Halpern, Benjamin S.
ABSTRACT: Understanding the dynamics of species range edges in the modern era is key to addressing fundamental biogeographic questions about abiotic and biotic drivers of species distributions. Range edges are where colonization and extirpation processes unfold, and so these dynamics are also important to understand for effective natural resource management and conservation. However, few studies to date have analyzed time series of range edge positions in the context of climate change, in part because range edges are difficult to detect. We first quantified positions for 165 range edges of marine fishes and invertebrates from three U.S. continental shelf regions using up to five decades of survey data and a spatiotemporal model to account for sampling and measurement variability. We then analyzed whether those range edges maintained their edge thermal niche—the temperatures found at the range edge position—over time. A large majority of range edges (88%) maintained either summer or winter temperature extremes at the range edge over the study period, and most maintained both (76%), although not all of those range edges shifted in space. However, we also found numerous range edges—particularly poleward edges and edges in the region that experienced the most warming—that did not shift at all, shifted further than predicted by temperature alone, or shifted opposite the direction expected, underscoring the multiplicity of factors that drive changes in range edge positions. This study suggests that range edges of temperate marine species have largely maintained the same edge thermal niche during periods of rapid change and provides a blueprint for testing whether and to what degree species range edges track temperature in general. Abstract : Using decades of survey data from three North American marine regions, we tested whether marine species' range edges maintained constant summer or winter temperatures over time. Of 165 range edges, 88% stayed within the same summer or winter temperatures (or both), suggesting that marine range edges may be tracking their thermal niches.